Pulmonary amyloidosis with impaired gas transfer. Issue 5 (September 1972) - Crosbie, W. A.; Lewis, M. L.; Ramsay, I. D.; Doyle, D.
Abstract : This is the report of a patient with multiple myelomatosis in whom secondary amyloid infiltration of the lung produced impairment of gas transfer and death from respiratory failure.